Antioxidant effect of blueberry flour on the digestibility and storage of Bologna-type mortadella. (January 2023) - Biasi, Vanessa; Huber, Eduardo; de Melo, Ana Paula Zapelini; Hoff, Rodrigo Barcellos; Verruck, Silvani; Barreto, Pedro Luiz Manique
Graphical abstract: Highlights: Blueberry flour (BF) had a high content of phenolic acids, mainly the chlorogenic. The antioxidant activity of BF was maintained after drying thermal processing. BF acted as a synthetic antioxidant substitute in Bologna-type mortadella. BF mortadella polyphenols increased after in vitro digestion. Abstract: The aim of the study was to add blueberry flour (BF) to Bologna-type mortadella as a natural antioxidant and to evaluate its activity during in vitro digestion and refrigerated storage. Five treatments of mortadella were prepared: without antioxidant, with sodium erythorbate and with the addition of three levels of BF: 0.05 %, 0.075 % and 0.1 %. Twenty-three phenolic compounds were quantified in blueberry fruits and twenty-eight in BF, with prevalence of chlorogenic acid. The presence of BF did not affect the proximal composition of the mortadella, but it had a small effect on pH, hardness (texture profile) and instrumental color, as well as reduced lipid oxidation during refrigerated storage (2–8 °C) for 90 days. During in vitro digestion, the addition of BF increased the content of total phenolic compounds and the antioxidant activity of mortadella (p < 0.05), among all simulated stages. At a concentration of 0.05 %, BF can be used as a synthetic antioxidant substitute in Bologna-type mortadella, enhancing the use of blueberry fruits in the form of flour and enriching the product with natural antioxidants.